STRATEGI PENGEMBANGAN BUDAYA RELIGIUS DALAM MEMBENTUK KARAKTER PESERTA DIDIK DI MA MU’ALLIMAT MALANG - Muhammad Ilham Adiyanto; Rosichin Mansur; Fita Mustafida (VICRATINA, 2019)
The development of religious culture is one of the most urgent ways to familiarize and give examples to students affecting all their actions and actions. This will help the purpose of education, where education has the goal of developing human potential to become a perfect soul . this study will discuss the strategy of developing religious culture in shaping the character of students at the MA Mu’allimat Malang. To achieve these objectives, researchers conducted research with a type of qualitative research with a type of case study research. This research was conducted at MA Mu’allimat Malang. procedure for data collection is done using the method of observation, interviews and documentation. Data analysis techniques in this study used descriptive reflective thinking data analysis, with steps namely data reduction, data display and verification. Checking the validity of the data using the member check, followed by the triangulation technique. Keywords: Religious Culture, Character of Students.